If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(3) = 6x + -7 Reorder the terms for easier multiplication: 3f = 6x + -7 Reorder the terms: 3f = -7 + 6x Solving 3f = -7 + 6x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by '3'. f = -2.333333333 + 2x Simplifying f = -2.333333333 + 2x
| 4p^2+8p-74=3 | | 30x=62 | | 30x=2 | | 6m/8=19/20 | | (2x-1)+(4x+2)= | | x^2+2x-58=0 | | 7a+8a=-15 | | 3u/4=7/10 | | 5x-3x=5-3(x+5) | | 2*w+24=92 | | 1x+3y=15 | | (20+x)12=350 | | y=4(1/2x-1) | | 3×1/4 | | 2*18+24=f | | 105/3 | | 2*15+24=f | | 6(2n+5)=6(8n+3)+3 | | 9x-(2x-3)=2(x+1)+4x | | 2*12+24=f | | 7x-5=3x+14 | | 5x+3=2y-3x+5 | | -5u-17=-3(u-1) | | 3x+4(35-x)=35 | | 25x+65=29x+25 | | Cosx=sin(2x+15) | | 6x-2(x-9)=5(2x+1) | | 2x+30=16x-12 | | 0.5x+0.3(15)=.2 | | (x+4)*(x-1)=2x(x+4) | | 1.5(5x-12)+2=44 | | 5(x-8)-5=-6(-3y+8)-x |